If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+18x-1=6(4x+3)
We move all terms to the left:
6x+18x-1-(6(4x+3))=0
We add all the numbers together, and all the variables
24x-(6(4x+3))-1=0
We calculate terms in parentheses: -(6(4x+3)), so:We get rid of parentheses
6(4x+3)
We multiply parentheses
24x+18
Back to the equation:
-(24x+18)
24x-24x-18-1=0
We add all the numbers together, and all the variables
-19!=0
There is no solution for this equation
| 348=24x | | 55x+2,045x-49=42(50x+72) | | 12-t5,t=3 | | 9r+2r-9r-r=18 | | 1=u/6 | | 55x+2,045-49=42(50x+72) | | 13-y=-20y+10-16 | | 0.5/12=x/5.25 | | (3x+4)+(5x)=180 | | 8+4x=2(−x+6)−22 | | 3(6d+1)+5=-10d+16+28d | | 5=2g-(-1) | | k/27=12 | | 6x-19+3x-32=180 | | 1/x^2=(1+x)^256 | | 4w-2w+2w+w=20 | | 4x-1=-7x+3 | | -6.24+17.1w=8.7+18w | | 65+m+58=180 | | 77=-5/2y | | q/26=18 | | -13/3y-6=-11 | | 6/3z=-2 | | 18m=234 | | -5=j/2-7 | | 9.75x+1.00=40 | | y=6(1)-11 | | s-(-26)/7=9 | | 90+31=x | | c/8=21 | | 5x+1=-3x-9 | | 9b–8=10 |